Tax competition: greenfield investment versus mergers and acquisitions - Johannes Becker; Clemens Fuest (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper, we analyze tax competition in a model where investor firms have the choice between two types of investment, greenfield investment and mergers and acquisitions. We show that the coexistence of these two types of investment intensifies tax competition in comparison to the case where there is only greenfield investment. If a specific tax on acquisitions is available, this result changes. Then, tax competition is mitigated compared to the pure greenfield case. The existence of an acquisition tax may even lead to corporate overtaxation.
Keywords: H25; F23; 330; corporate taxation; mergers and acquisitions; tax competition; Unternehmensbesteuerung; Steuerwettbewerb; Direktinvestition; Übernahme; Fusion; Theorie